Optimization of oxidative desulfurization of gas condensate via response surface methodology approach. (1st February 2019) - Pouladi, Babak; Fanaei, Mohammad Ali; Baghmisheh, Gholamreza
Abstract: In the present research, modeling and optimization of a new method of oxidative desulfurization (ODS) of sour gas condensate has been done. In the ODS process, combination of H2 SO4, HNO3, and NO2 as oxidizing agents at varying concentrations followed by extraction, was applied. A response surface methodology (RSM) was deployed for the experimental design, model development, and testing the validity of the model using Design-Expert ® software. Moreover, investigation of the main effects as well as the combined effects of the process parameters on the response was also carried out. For the first time in a gas-liquid ODS system, a mixing-assisted oxidative desulfurization (MAOD) approach was considered by applying a shear mixer. The value greater than 0.9 for R 2 of the sulfur removal data confirmed that the quadratic equation properly fitted the experimental data. Optimization results predicted that the implementation of the process at 0.593, 0.682, and 0.264 mol of H2 SO4, HNO3, and NO2, respectively, for a sample of 1500 gr gas condensate, would result in the minimum residual sulfur content of 100.9 ppmw (95.61% sulfur removal) while the actual value of sulfur removal at the predicted optimized conditions was determined as 102 ppmw (95.56% sulfur removal). With respect to the obtained results, the developed model was in good agreement with the experimental results.